Distributed Place Leadership in the Global South: An integrated strategic framework for public value at Universidad Cooperativa de Colombia (UCC) - Fumasoli, Tatiana (Rastros Rostros, 2026)
This paper provides a strategic roadmap for the Universidad Cooperativa de Colombia (UCC) as it transitions towards its Plan Estratégico Nacional 2030. Against a backdrop of profound systemic stratification in Colombian higher education and the enduring legacy of internal conflict, the institution faces the dual imperative of deepening its territorial relevance while expanding its global engagement. Challenging traditional centre-periphery models, this analysis argues that for a private, multicampus, cooperative institution in the Global South, internationalisation must be reconceptualised not as a pursuit of reputational prestige, but as a structural mechanism for equity, resource mobilisation, and local problem-solving. Drawing on the theoretical framework of Place Leadership, the paper audits UCC’s current capacity—characterised by a decentralised network of 16 campuses across 19 cities and a student body primarily drawn from low and medium-low socioeconomic backgrounds. It identifies a strategic opportunity for UCC to function as a “Distributed Place Leader,” linking fragmented regional innovation systems into a cohesive national network. The document concludes with a set of actionable policy recommendations focused on networked governance, inclusive internationalisation (Internationalisation at Home and Collaborative Online International Learning), and the consolidation of solidarity ecosystems. These strategies position UCC to lead not merely as an educational provider, but as a Civic University of Social Innovation, capable of driving territorial resilience and democratising access to the global knowledge economy.
Keywords: Civic university; multicampus governance; inclusive Internationalisation; social solidarity economy; territorial resilience; post-conflict reconstruction